PENYULUHAN DAN EDUKASI MANAJEMEN NYERI DAN KRAM EKSTREMITAS BAWAH PADA KOMUNITAS PEMAIN TENIS LAPANGAN FARMASI UMS - Rhama Syuhada Sujak; Allysha Adzra Zahra Senjaya; Afrilia Saras Pratamasiwi; La Ode Abdal Idrus (Jurnal Pengabdian Masyarakat, 2022)
Background: Field tennis is a small ball sport which is a sport that uses the lower extremities actively and is also popular among the public. Objective: This activity aims to increase public understanding of lower extremity muscle pain and cramps. Methods: The activity chosen to deliver education is counseling which is packaged with the lecture method using poster media. Evaluation of knowledge about pain and muscle cramps in the lower extremities was carried out using a questionnaire both before and after the process of delivering the material. Results: Based on the responses of the activity participants, namely a total of 5 respondents, it was found that before the delivery of the material the participants had knowledge in the poor category and after the delivery of the material the scoring of the questionnaire results increased to the good category. Conclusion: In conclusion, education and counseling of lower extremity muscle pain and cramps in tennis players have a good impact in helping to increase the knowledge of community members regarding lower extremity muscle pain and cramps.